An economic evaluation of a weight loss intervention program for people with serious mental illnesses taking antipsychotic medications - Meenan, Richard T. (Adm Policy Ment Health, 2016)
Individuals with serious mental illnesses suffer from obesity and cardiometabolic diseases at high rates, and antipsychotic medications exacerbate these conditions. While studies have shown weight loss and lifestyle interventions can be effective in this population, few have assessed intervention cost-effectiveness. We present results from a 12-month randomized controlled trial that reduced weight, fasting glucose, and medical hospitalizations in intervention participants. Costs per participant ranged from $4,365 to $5,687. Costs to reduce weight by one kilogram ranged from $1,623 to $2,114; costs to reduce fasting glucose by one mg/dL ranged from $467 to $608. Medical hospitalization costs were reduced by $137,500.